Arabic translation and validation of SNOT-22 - Samy Elwany; Ahmed Atef; Ahmed A. Ibrahim; Ahmed S. Ismail; Wael K. Hussein; Ahmed S. Youssef; Mohamed Elwany; Remon Bazak (The Egyptian Journal of Otolaryngology, 2017)
Abstract Objective The objective of the study was to translate the Sino-Nasal Outcome Test 22 (SNOT-22) into Arabic and to check its reliability and validity in Arabic-speaking patients. Patients and methods The study included 178 patients with confirmed chronic rhinosinusitis (CRS) and 95 asymptomatic individuals as a control group. All participants completed the Arabic SNOT-22 (A-SNOT-22) questionnaire. The scores of the two groups were compared for validity analysis. Eighty-two patients completed the questionnaire twice, 1 week apart, for test-to-test reliability analysis. The A-SNOT-22 scores of 60 CRS patients were correlated with Lund–Mackay scores for criterion validity analysis. The preoperative and postoperative scores of 73 patients were compared for responsiveness analysis. Results All participants completed the questionnaire with no or minimal assistance. Internal consistency (α=0.90) and test-to-test reliability (intraclass correlation=0.78) were good. The differences between the scores of CRS patients and asymptomatic individuals were significant (P<0.005). There was a positive moderate correlation between A-SNOT-22 and Lund–Mackay scores. Preoperative A-SNOT-22 scores were significantly higher than postoperative scores. Conclusion A-SNOT-22 questionnaire is a reliable and valid outcome measure for CRS patients. The questionnaire is responsive to changes in the state of the disease and is recommended for clinical practice and outcome research.